Design and Construction of Phosphorus Removal Structures for Improving Water Quality - Penn, Chad J. (Springer International Publishing, 2018)
The purpose of this book is to introduce the phosphorus (P) removal structure as a new BMP for reducing dissolved P loading to surface waters from non-point source pollution, provide guidance on designing site-specific P removal structures, and provide instruction on use of the design software, "Phrog" (Phosphorus Removal Online Guidance). The book initially provides a review of the nature and sources of non-point source P pollution, examines short and long term solutions to the problem, and provides detailed theory on design and operation of the P removal structure. As with many areas of study, one of the best methods of communicating concepts is through illustrations and examples. This book is no exception; several years of experience in studying P sorption and constructing P removal structures at multiple scales and settings is utilized for providing real examples and applications. With an understanding of the P removal structure established, the reader is instructed on how to obtain all of the necessary inputs for properly designing a site-specific P removal structure for meeting a desired lifetime and performance, or predict the performance and lifetime of a previously constructed P removal structure. For the readers who already possess the Phrog design software or are interested in obtaining it, one chapter is dedicated to detailed use of the software as demonstrated with various examples of structure design and also prediction.